(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Post-apartheid South Africa struggles to develop a sense of social cohesion and nationhood, which remain largely unfulfilled constitutional imperatives. The pre-amble of the post-apartheid constitution (1996) recognises amongst other things, the “injustices of our past, ... that South Africa belongs to all who live in it, and (to) lay the foundations for a democratic and open society”. The Curriculum and Assessment Policy Statement (CAPS) creates space in the history curriculum to address democratic citizenship and social cohesion. Due to a racially fragmented history, South African nationhood is still a future-oriented project for the attention of the state, and in the context of this study, the education sector. This article reports on an exploratory history lesson, teaching democratic citizenship for social development and nation-building. The lesson was presented to grade 10 learners at a township high school in North Pretoria. A “critical literary pedagogy” (CLP) approach was employed as a pathway to teaching social cohesion and nationhood, through historical reflection and imagination. A CLP approach has a commitment to change and employs literary texts as learning material. The article responds to the research question: What is the potential role of CLP as an approach to the teaching of democratic citizenship in a post-apartheid classroom? As conceptual framework “cosmubuntuism”, a combination of cosmopolitan and Ubuntu values provides a theoretical lens to understand learners’ imaginations of democratic citizenship. Five dominant themes emerged from the data, confirming the potential of CLP, but alerting to contradictory and critical outcomes of the lesson. Recommendations are suggested, inter alia, for teacher education institutions to use the CLP approach to address the didactical needs of history teachers to cultivate social cohesion and nationhood in the post-apartheid South African history classroom.